2006
DOI: 10.1021/jp061979z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Fabrication and Enhanced Photocatalytic Activities of 3D-Ordered Films of Titania Hollow Spheres

Abstract: Facile and effective approaches were developed to fabricate 3D-ordered films of titania hollow spheres with different sphere diameters. The shell thickness of the sphere was adjusted in the range of 20-40 nm by changing the casting cycle of the titania precursor. The photonic stop band was observed for the 3D-ordered film and was tunable by the sphere diameter and the shell thickness. The stop band shifted from 930 to 547 nm. Crystal violet dye adsorbed on the film exhibited more than two times higher absorban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 28 publications
0
120
1
Order By: Relevance
“…[82] Unlike previous coating schemes, this novel method ensures uniform coating by physically limiting the amount of sol-gel shell precursor locally available to each template particle, although in theory formation of interconnected hollow particles is highly possible. [83,84] Based on a similar concept of limiting precursor in a cavity, Jiang et al demonstrated an elegant, general nanoscale ''lost-wax'' method for general preparation of hollow spheres and their corresponding colloidal crystals. [85] The method involves two replication steps.…”
Section: Templating Against Colloidal Crystals and The Lost-wax Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[82] Unlike previous coating schemes, this novel method ensures uniform coating by physically limiting the amount of sol-gel shell precursor locally available to each template particle, although in theory formation of interconnected hollow particles is highly possible. [83,84] Based on a similar concept of limiting precursor in a cavity, Jiang et al demonstrated an elegant, general nanoscale ''lost-wax'' method for general preparation of hollow spheres and their corresponding colloidal crystals. [85] The method involves two replication steps.…”
Section: Templating Against Colloidal Crystals and The Lost-wax Approachmentioning
confidence: 99%
“…Hollow TiO 2 nanospheres have been reported by several groups to exhibit high activities and as such have been targeted as the active electrode component in high-efficiency dye-sensitized solar cells. [84,369,370] Metal oxides hollow spheres (e.g., TiO 2 ) have also been widely investigated for photocatalytic degradation of organic pollutants. [228,253,277,281,303,371] a-Fe 2 O 3 hollow nanospheres, for example, have been shown to yield improved photocatalytic performance over a-Fe 2 O 3 nanocrystals in oxidation of salicylic acid.…”
Section: Catalysis and Sensingmentioning
confidence: 99%
“…Because some PCs have a connected 3D network of voids, for example, the inverse opal structure, 3 the highly porous character presents opportunities for novel applications including, organic solar cells, [4][5][6] and photocatalysts for decomposing chemical waste. 7,8 Moreover, it is predicted that PCs could be applied to hydrogen production using photoelectrolysis. 9 Electrochemical reactions can be optimized by considering both the photonic performance and the proper 3D structure.…”
Section: Semicrystalline Woodpile Photonic Crystals Without Complicatmentioning
confidence: 99%
“…[21] An admirable solution to enhance the photocatalytic activity of TiO 2 is a combination of two methods: (1) the absorption ability of light should be enhanced and (2) the separation of the electron-hole pairs should be improved. Many efficient methods to improve the photocatalytic efficiency of TiO 2 have been proposed to solve these two problems, such as increasing the surface/bulk defect ratio, [22] surface fluorination of TiO 2 , [23,24] utilizing the photocatalytic enhancement of slow photons in photonic crystals, [25,26] and the formation of nanocomposites. [27] The most popular solution proposed by other researchers to deal with the problem [28,29] is the simultaneous modification of TiO 2 with metals or metallic oxides.…”
Section: Introductionmentioning
confidence: 99%